2016
DOI: 10.1016/j.envpol.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Throughfall and bulk deposition of dissolved organic nitrogen to holm oak forests in the Iberian Peninsula: Flux estimation and identification of potential sources

Abstract: Deposition of dissolved organic nitrogen (DON) in both bulk precipitation (BD) and canopy throughfall (TF) has been measured for the first time in the western Mediterranean. The study was carried out over a year from 2012 to 2013 at four evergreen holm oak forests located in the Iberian Peninsula: two sites in the Province of Barcelona (Northeastern Spain), one in the Province of Madrid (central Spain) and the fourth in the Province of Navarra (Northern Spain). In BD the annual volume weighted mean (VWM) conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 64 publications
9
22
0
1
Order By: Relevance
“…The amount of organic N as a proportion of total N (inorganic + organic N) N deposition has been found to be about a third in mostly rural locations across 160 studies worldwide and 58 studies in North America (29% and 35%, respectively; Cornell, ). A similar proportion of organic N in total deposition has also been found in urban areas in studies around the world (Araujo et al, ; Chen et al, ; de Souza et al, ; González‐Benitez et al, ; He et al, ; Izquieta‐Rojano et al, ; Li et al, ; Matsumoto et al, ). There have been a handful of studies in the U.S. measuring organic N deposition in small towns in Connecticut and North Carolina, in winter precipitation in Salt Lake City, Utah and in Miami, Florida; four of these studies either do not report organic N deposition rates or do not report organic rates in the urban sites individually, and the others report the percentage of organic N in total N as below 20% (Brezonik et al, ; Hall et al, ; Keene et al, ; Luo et al, ; Nadim et al, ; Zamora et al, ).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…The amount of organic N as a proportion of total N (inorganic + organic N) N deposition has been found to be about a third in mostly rural locations across 160 studies worldwide and 58 studies in North America (29% and 35%, respectively; Cornell, ). A similar proportion of organic N in total deposition has also been found in urban areas in studies around the world (Araujo et al, ; Chen et al, ; de Souza et al, ; González‐Benitez et al, ; He et al, ; Izquieta‐Rojano et al, ; Li et al, ; Matsumoto et al, ). There have been a handful of studies in the U.S. measuring organic N deposition in small towns in Connecticut and North Carolina, in winter precipitation in Salt Lake City, Utah and in Miami, Florida; four of these studies either do not report organic N deposition rates or do not report organic rates in the urban sites individually, and the others report the percentage of organic N in total N as below 20% (Brezonik et al, ; Hall et al, ; Keene et al, ; Luo et al, ; Nadim et al, ; Zamora et al, ).…”
Section: Introductionsupporting
confidence: 63%
“…Moreover, the tree canopy is known to augment rates of nutrient inputs to the ground, as well as to waterways (Ormerod et al, ; Reynolds et al, ), in nonurban areas through capturing dry deposition (Lovett & Lindberg, ) and the production of pollen (Kopáček et al, ), insect frass (le Mellec et al, ), and other biological material (Osono et al, ; Pedersen & Bille‐Hansen, ). Studies in urban areas have reported elevated rates of throughfall (inputs beneath tree canopy) compared to bulk (inputs beneath open sky) deposition (Juknys et al, ; Michopoulos et al, ; Kimura et al, ; Fang et al, ; Bettez & Groffman, ; Tulloss & Cadenasso, ; Izquieta‐Rojano et al, , Ponette‐González et al, 2017). In many studies, however, throughfall has been measured at a limited number of urban sites and/or has not been collocated with bulk measurements for direct comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…3). These ephemeral inputs, among other effects, can trigger pulses of NO emissions from soil (Homyak and Sickman, 2014) or provoke a flushing of inorganic N to ground-or stream waters if the pulse occurs when plants and soil communities are not able to use this dissolved N (like at the end of the summer, when they are withstanding drought stress). This effect, known as the asynchrony hypothesis (Meixner and Fenn, 2004), is corroborated in TC, where relatively high concentrations of NO 3 À in the soil water (up to 28.15 and 4.90 mg NO 3 -N l À1 at 20 and 40 cm depth, respectively, using tension lysimeters) have been found after these pulses of N during late-summer and early-autumn, but not during the early spring of 2012, when understory annual pastures were emerged and growing and soil communities were active.…”
Section: Nitrogen Deposition In Holm Oak Forestsmentioning
confidence: 99%
“…The precipitation in CA was much more alkaline (with a mean pH of 7.3 and a mean alkalinity of 141.1 µeq l -1 ) than in CB or TC (with mean pH of 6.3 and 6.0; and mean alkalinity of 67.6 and 27.5 µeq l -1 , respectively) during the study period (Aguillaume, 2015). It may therefore occur that carbonates and bicarbonates present in the rain in this site increased the pH of the extracts provoking the loss of NH 4 + via volatilization of NH 3 before the analysis (Cape et al, 2012;Izquieta-Rojano et al, 2016). However, such high values may also be originated partially from hydroxide anions which could be leached from the IER; and this possibility and the processes involved merit further study.…”
Section: Variability Of the Measurementsmentioning
confidence: 99%
“…A study in the framework of the EDEN project (Izquieta-Rojano et al, 2016) showed that DON may constitute another factor driving the uncertainties in the knowledge of the N cycle in the Region, since it was found to contribute from 34% to 56% to the bulk deposition of dissolved N for the four study sites of the project and from 38% to 72% to the throughfall deposition.…”
Section: Bulk and Throughfall Deposition Of Organic Nmentioning
confidence: 99%